Climate change and bird reproduction: warmer springs benefit breeding success in boreal forest grouse. Issue 1866 (8th November 2017) - Wegge, Per; Rolstad, Jørund
Abstract : Global warming is predicted to adversely affect the reproduction of birds, especially in northern latitudes. A recent study in Finland inferred that declining populations of black grouse, Tetrao tetrix, could be attributed to advancement of the time of mating and chicks hatching too early—supporting the mismatch hypothesis. Here, we examine the breeding success of sympatric capercaillie, T. urogallus, and black grouse over a 38-year period in southeast Norway. Breeding season temperatures increased, being most pronounced in April. Although the onset of spring advanced nearly three weeks, the peak of mating advanced only 4–5 days. In contrast to the result of the Finnish study, breeding success increased markedly in both species (capercaillie: 62%, black grouse: 38%). Both brood frequency and brood size increased during the study period, but significantly so only for brood frequency in capercaillie. Whereas the frequency of capercaillie broods was positively affected by rising temperatures, especially during the pre-hatching period, this was not the case in black grouse. Brood size, on the other hand, increased with increasing post-hatching temperatures in both species. Contrary to the prediction that global warming will adversely affect reproduction in boreal forest grouse, our study shows that breeding success was enhanced in warmer springs.